Digital Image Storage System Based on USB and NAND Flash - Yongjun Cui; Wei Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Focusing on the storage of large number of digital image information, a system is designed which based on USB bus and NAND-type FLASH using alternating two-plane page program. The aim of this study is to short the writing-reading FLASH time and improve the transmission of data in order to enhance the efficiency of the system. In hardware implementation, the paper introduced the interface between every module especially the USB connection. In software, detailed analysis of the key technology about the alternating two-plane page program was shown. By commissioning, the speed of data stored in the FLASH is 30MB/s, achieving fast data storage and accurate feedback purposes, making sure that the data was reliable.